Transcutaneous delivery of sodium bicarbonate increases intramuscular pH - Gibson, Brandon M.; Needham, Karen Wiedenfeld; Kaiser, Brendan W.; Wilkins, Brad W.; Minson, Christopher T.; Halliwill, John R. (Frontiers in Physiology, 2023)
Introduction: Oral bicarbonate loading improves the buffering of metabolic acidosis and may improve exercise performance but can also result in gastric distress. Momentous’ PR Lotion contains a novel composition intended to provide a transdermal delivery vehicle for sodium bicarbonate which could allow the same ergogenic effect without the gastric distress. The present study explored the effect of transdermal delivery of sodium bicarbonate in a resting condition. Methods: We measured the pH from intramuscular dialysate, via microdialysis, of the vastus lateralis during a 2 h application of PR Lotion (40 g of lotion per leg) in 9 subjects (3 women, 6 men). Venous blood samples were obtained for serum pH before and after application. A placebo time control was also performed in 4 subjects (2 women, 2 men). We hypothesized that PR Lotion application would increase pH of intramuscular dialysate. Results: PR Lotion resulted in a rise in pH of 0.13±0.04 units (p < 0.05), which translates to a 28% reduction in [H+]. Increases in serum pH were smaller (~9%) yet consistent (p < 0.05). In contrast, placebo time control pH tended to decrease (p = 0.08). The effect of PR Lotion on pH tended to correlate with the dose per kg body weight of each individual (r = 0.70, p = 0.08). Conclusions: These observations support the idea of transdermal bicarbonate delivery impacting pH buffering both systemically and intramuscularly. Further work investigating these potential benefits in an exercising model would be critical to establishing PR Lotion’s utility as an ergogenic aid.